Prospects for digitalization of sustainable development projects in the Russian Federation - I. V. Pashkovskaya; B. B. Rubtsov; N. A. Amosova; O. S. Rudakova (Вестник университета, 2023)
Green bonds have become the most notable innovations in the field of sustainable financing over the past 10 years. The article discusses the problems of issuing and circulation of such financial market instruments, examines the opportunities that modern financial technologies provide for the development of this market segment. Technologies for investing in green bonds and sustainable development bonds remain burdensome and technologically complex, as they involve going through many stages and attracting a significant number of participants. In addition, to date, there has not been a liquid and transparent market for retail investors, and economic sanctions against Russia cut off the country from the financial markets of other countries for an indefinite time. However, the tools of sustainable development can now be successfully applied if innovative technologies such as blockchain technologies, smart contracts, the Internet of things and digital assets are used. The purpose of the study is to formulate recommendations for the progress of the sustainable development system in Russia, as well as to propose a mechanism for the tokenization of sustainable development bonds to attract and place funds from small investors in order to solve social and environmental problems of the Russian economy.